PENERAPAN MEDIA VISUAL DALAM PENGEMBANGAN KETERAMPILAN BERBICARA SISWA KELAS V.B SDN 151/IV KOTA JAMBI - Gessy Frischa Oktavia; Indriyani; Ugi Nugraha; Urip Sulistiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The primary objective of this research was to investigate the enhancement of oral communication proficiency among fifth-grade students at SD Negeri 151/IV Kota Jambi through the application of instructional media. The study employed a Classroom Action Research methodology, focusing on a cohort of 28 fifth-grade students during the 2024/2025 academic year. Data collection was conducted utilizing observational techniques and performance assessments. The research employed both quantitative and qualitative analytical approaches to evaluate the students' speaking skill progression. The research findings reveal a significant enhancement in speaking proficiency among fifth-grade students at SD Negeri 151/IV Kota Jambi through the implementation of image-based media. The improvement is evident across multiple speaking skill dimensions, including pronunciation accuracy, intonation modulation, vocabulary selection, discourse coherence, verbal confidence, linguistic fluency, communicative attitude, and thematic comprehension. The progression is directly reflected in both the learning process and students' performance metrics.Comparative analysis of assessment scores demonstrates a clear developmental trajectory. The pre-intervention baseline showed an average performance of 69.42, categorized as moderately skilled, with a student achievement rate of 36%. Following the first instructional cycle, the average score increased to 73.32, maintaining a moderate skill classification. The second intervention cycle yielded more remarkable outcomes, with the average score climbing to 88.82 and student completeness percentage reaching 79%, now classified as a very good performance level. Data interpretation conclusively indicates that the strategic application of image media in speaking skill instruction for fifth-grade students at SD Negeri 151/IV Kota Jambi effectively enhanced students' communication capabilities, providing a robust pedagogical approach to language learning development.